Field study of indoor environment quality in an open atrium with ETFE membrane in a healthcare facility - Tang Haida; Li Chunying; Ding Jianhua (E3S Web of Conferences, 2019)
The hospital street is widely utilized in the modern health care facilities as a main traffic streamline to connecting all of the outpatient rooms and treatment departments for easy access. This study investigate the indoor environment quality of a typical hospital street, i.e., a high space atrium with ETFE membrane structure in the top. The investigation combines the on-site measurement and subjective survey. The results indicates that the indoor air temperature in the atrium reaches up to 32.6oC in a summer day causing thermal discomfort according to ASHRAE 55. The CO2, PM2.5, TVOC concentration in the hospital street comply with the Chinese standard for hospitals. The illumination in the corridors around the atrium is below the threshold of Chinese standard, i.e., 100 lux. Due to the vibration of the light ETFE membrane structure, the noise level in rainy days is as high as 79.5 dB which causes acoustic discomfort of occupants. This study is beneficial for the design of the hospital street design with the ETFE membrane structure.